Effect of the application of a biofertilizer on the yield of forage oats (Avena sativa L.) in the southern Durango, Mexico - Aguirre-Córdova, Oscar; Valencia, Roberto; Ortíz, Ixchel; Chávez, Jorge; Araiza, Elia; Pámanes-Carrasco, Gerardo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
It is a priority to identify more efficient ways to fertilize crops without harming the soils. Biofertilizers obtained from the anaerobic digestion of manure can emerge as an ecological alternative in crop production. This study aimed to evaluate the yield and nutritional characteristics of oats (Avena sativa L.) fertilized with different doses of biofertilizer (Biol) through foliar application. In southern Durango, Mexico, four doses of Biol were applied: 0, 220, 440, 660 and 880 L.ha-1, corresponding to treatments T1, T2, T3, T4, and T5, respectively, using a completely randomized block design. The crude protein (CP) content was similar among treatments (p>0.05); Meanwhile, neutral detergent fiber (NDF), acid detergent fiber (ADF), and phosphorus (P) decreased with the maximum doses of Biol (p<0.05). Regarding in vitro dry matter digestibility (IVDMD) differences were found (p<0.05). Fresh weight (FW) and dry weight (DW) yields increased with the higher doses of Biol, achieving higher values of 25.50 and 7.05 t.ha-1, respectively. Additionally, the application of the biofertilizer Biol increased oat yield and improved some nutritional values of the forage. These results suggest that Biol is a viable alternative to the use of chemical fertilizers, promoting sustainable agriculture and contributing to the mitigation of the negative environmental impact generated by chemical fertilizers.